MRI findings in organophosphate-induced delayed neuropathy: A case report - Salma Moussaoui; Salma El Ouadih; Anas Orgi; Aicha Merzem; Hasna Belgadir; Omar Amriss; Nadia Moussali; Naima El Benna (Radiology Case Reports)
Organophosphate poisoning, including malathion ingestion, is a common method of suicide in some regions. This case involves a 24-year-old male who ingested malathion in a suicide attempt. Four weeks postingestion, the patient developed progressive neurological deterioration with motor deficits, seizures, and altered consciousness. MRI revealed diffuse hyperintensities in the corpus callosum, subcortical white matter, and other central nervous system structures, consistent with organophosphate-induced delayed neuropathy (OPIDN). Despite corticosteroid therapy, the patient's condition worsened due to septic shock, leading to death. This case highlights the importance of MRI in diagnosing OPIDN which remains rare and poorly documented in the literature. It also emphasizes the need for timely imaging to guide treatment and monitor disease progression.